Improving Student Learning Outcomes by Applying the Blanded Learning Method in Local History Subjects at SMA Negeri 1 Gebog in the New Normal Period - Siswanti, Indri (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
The purpose of this study is to describe learning local history using the Blended Learning method at SMA Negeri 1 Gebog Masa New Normal. This type of research is classroom action research. This research was conducted at SMA Negeri 1 Gebog Kudus with research subjects in class X MIPA 5. The results of this study were learning local history using the Blended Learning method at SMA Negeri 1 Gebog Masa New Normal could improve learning outcomes. The student's ability to answer the post-test questions given, for students who are PTM in class an average of 78.05. While the ability of students who study at home is an average of 73.05. Both PTM and PJJ students the average score has exceeded the KKM set by the school, which is 65.